Use of Oral Anticoagulants in Patients with Atrial Fibrillation: Preliminary Data from the Italian Atrial Fibrillation (ITALY-AF) Registry - Fabio Angeli; Gianpaolo Reboldi; Giancarlo Agnelli; Giuseppe Ambrosio; Alessandro Capucci; Giovanni Carreras; Claudio Cavallini; Adriano Murrone; Gaetano Vaudo; Gianluca Zingarini; Paolo Verdecchia (Clinics and Practice, 2023)
Background: Atrial fibrillation (AFIB), the most frequent cardiac arrhythmia, is a major risk factor for stroke, heart failure, and death. Because of the recent advances in AFIB management and the availability of new oral anticoagulants (OACs), there is a need for a systematic and predefined collection of contemporary data regarding its management and treatment. Methods: The objective of the ongoing ITALY-AFIB registry is to evaluate the long-term morbidity and mortality in patients with AFIB and to verify the implementation of the current guidelines for stroke prevention in these patients. The registry includes consecutive in- and out-patients with first diagnosed, paroxysmal, persistent, or permanent AFIB. In patients in sinus rhythm at entry, the qualifying episode of AFIB, confirmed by ECG diagnosis, had to have occurred within 1 year before entry. The clinical record form is web-based and accessible by personal keyword. Results: Enrolment into the registry started in the year 2013. In a current cohort of 2470 patients (mean age 75 ± 11 years, males 56%), the mean CHA2DS2-VASc score was 3.7 ± 1.8, and the mean HAS-BLED was 1.6 ± 0.9. There were no significant sex differences in the AFIB subtypes. At the end of the inclusion visit and after receiving knowledge of the web-based electronic estimate of risk for stroke and bleeding, the proportion of patients discharged with OACs was 80%. After exclusion of patients with first diagnosed AFIB (n = 397), the proportion of patients with prescription of OACs rose from 66% before the visit to 82% on discharge (p < 0.0001). Prescription of aspirin or other antiplatelet drugs fell from 18% before the visit to 10% on discharge (p < 0.0001). Conclusions: A web-based management of AFIB with automated estimation of risk profiles appears to favorably affect adherence to AFIB guidelines, based on a high proportion of patients treated with OACs and a substantial decline in the use of antiplatelet drugs.